HUBUNGAN PENGGUNAAN LKS (LEMBAR KERJA SISWA) DENGAN HASIL BELAJAR SISWA SMA PADA MATA PELAJARAN SEJARAH DI KOTA CIMAHI - Gustikasari, Vanny (2013)
This research is motivated from the importance of teaching history requires learning resources. History learning resource in question is LKS (Student Worksheet). The use of worksheets in the teaching of history has benefits such as minimizing the role of the teacher also allows the students to understand the material. LKS history that had been circulating developing impressed factual material is a summary of the book package. Based on the above issues, this study uses correlation research method aims to find the relationship between the use of worksheets with High School Student Results on Historical Subjects Cimahi. Variable use of worksheets are translated into sub-variables such as display LKS (X ₁), availability of LKS (X ₂), component LKS (X ₃), and form about LKS (X ₄) while the variable is not defined learning outcomes. Results of calculations using SPSS (Statistical Product and Service Solutions) version 18.0 for windows, the results of this study are received research hypothesis (H1), is accepted- positive and significant relationship between the use of Student Worksheet (LKS) with Student Learning Outcomes High School in Eye History Lesson in Cimahi with a low correlation coefficient. The low correlation between the use worksheets with Student Results occur due to many factors, one of which worksheets are used not made by the teacher concerned. Authors feel this research is not perfect, so expect no improvement in next research. Keyword : learning resources, student work sheet, learning outcomes Penelitian ini dilatarbelakangi dari pentingnya pembelajaran sejarah yang membutuhkan sumber belajar. Sumber belajar sejarah yang dimaksud adalah LKS (Lembar Kerja Siswa). Penggunaan LKS dalam pembelajaran sejarah memiliki manfaat diantaranya meminimalkan peran pengajar juga memudahkan peserta didik untuk memahami materi. LKS sejarah yang selama ini beredar mengembangkan materi yang faktual terkesan merupakan rangkuman dari buku paket. Berdasarkan dari permasalahan di atas, penelitian ini menggunakan metode penelitian korelasi bertujuan mengetahui besarnya hubungan antara penggunaan LKS dengan Hasil Belajar Siswa SMA pada Mata Pelajaran Sejarah di Kota Cimahi. Variabel penggunaan LKS dijabarkan ke dalam sub-variabel diantaranya tampilan LKS (X₁), ketersediaan sarana LKS (X₂), komponen LKS (X₃), dan bentuk soal LKS (X₄) sedangkan variabel hasil belajar tidak dijabarkan. Hasil perhitungan menggunakan program SPSS (Statistical Product and service Solution) versi 18.0 for windows, hasil penelitian ini adalah diterimanya hipotesis penelitian (H1), yaitu ada hubungan yang positif dan signifikan antara penggunaan Lembar Kerja Siswa (LKS) dengan Hasil Belajar Siswa SMA pada Mata Pelajaran Sejarah di Kota Cimahi dengan koefisien korelasi rendah. Rendahnya hubungan antara penggunaan LKS dengan Hasil Belajar Siswa terjadi karena banyak faktor, salah satunya LKS yang digunakan bukan dibuat oleh guru yang bersangkutan. Penulis merasa penelitian ini belum sempurna, sehingga diharapkan ada perbaikan pada penelitian selanjutnya. Kata kunci: Sumber belajar, LKS, hasil belajar.